Pemberdayaan Masyarakat untuk Memenuhi Kebutuhan Air Bersih di Kampung Ifale Distrik Sentani Kabupaten Jayapura - Bambang Suhartawan; Alfred B Alfons; Tanwir Tanwir; Dewi Anggraeni; Herman HI Tjolleng Taba; Yuyun Nuriah; Daawia Daawia (Jurnal Medika: Medika, 2025)
Community empowerment to meet clean water needs in Ifale Village, Sentani District, Jayapura Regency, is crucial given the declining water quality of Lake Sentani due to pollution. Despite having access to water sources, communities still rely on untreated water, leading to increased disease. This research aims to improve community access to clean water through the development of a local media-based filtration system. Methods used include community education, training, and advocacy to improve understanding and skills in water treatment. Results show a significant reduction in water quality parameters, such as turbidity and E. coli, as well as increased community awareness of the importance of water treatment. The formation of clean water management groups is a strategic step to ensure the program's sustainability. In conclusion, this program not only improves access to clean water but also empowers communities to manage water resources independently, enabling it to be implemented in other areas facing similar challenges.